COVID19 Prevalence in Germany – Chances and Challenges - T, Übner; U, Bohn; M, Hartmann; K, Schragner; E, Nestle; H, Arends; A, Eitelhuber; F, Krieger; G, Diez (Archives of Clinical and Biomedical Research, 2021)
Even one year after declaring a pandemic, the number of infections is still increasing. In order to prevent the further spread of SARS-CoV-2, public health interventions have been introduced globally. One major target is to avoid the overload of health care systems, especially for the most severely affected patients. According to the Robert-Koch-Institut (RKI), approximately 2.4 Mio people were infected with SARS-CoV-2 in Germany by the end of February 2021. This represents 2.92% of the German population. However, asymptomatic courses are underestimated. Studies so far focused mainly on identifying acute infected individuals as well as the clinical course of patients and vaccine development. As a consequence, in Germany, as in many other regions knowledge about the seroprevalence of SARS-CoV-2 and thus about the immune status of the population is lacking. Nevertheless, such data is urgently needed to understand the dynamics of the pandemic and hence to design interventions such as vaccination campaigns appropriately. In this work the anti-SARS-CoV-2-IgG immune status of 140 healthy blood donors from southern Germany, collected at the end of February 2021, was determined using the SERION ELISA agile SARS-CoV-2 IgG. In this cohort, 5.7 % were evaluated positive for SARS-CoV-2 specific IgG antibodies, suggesting a higher prevalence as expected.